PENGARUH MADRASAH KUFAH DALAM KITAB NAHWU YANG DIAJARKAN DI INDONESIA - Sa'diyah, Halimatus; Abdurahman, Maman; Sopian, Asep (Hijai - Journal on Arabic Language and Literature, 2021)
ØªÙ†Ø§Ù‚Ø´ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙƒÙˆÙØ© Ø§Ù„ØªÙŠ ÙƒØ§Ù† Ù„Ù‡Ø§ ØªØ£Ø«ÙŠØ± ÙƒØ¨ÙŠØ± Ø¹Ù„Ù‰ ØªØ·ÙˆØ± Ø§Ù„Ù„ØºØ© ØŒ Ø®Ø§ØµØ© ÙÙŠ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…ØµØ·Ù„ØØ§Øª ÙÙŠ ÙƒØªØ§Ø¨ Ø§Ù„Ù†ØÙˆ. Ø§Ø³ØªØ®Ø¯Ù…Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ø£Ø¯Ø¨ÙŠØ© ÙˆØ§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù†ÙˆØ¹ÙŠ Ù„Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙƒÙˆÙØ© Ø¹Ù„Ù‰ Ø§Ù„ÙƒØªØ§Ø¨ Ø§Ù„Ø°ÙŠ ÙŠØ³ØªØ®Ø¯Ù…Ù‡ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠÙˆÙ† Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ‡Ùˆ ÙƒØªØ§Ø¨ Ø§Ù„Ø¬Ø±Ù…ÙŠØ©. ÙˆØ£Ø¸Ù‡Ø±Øª Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ø§Ø¨Ù† Ø¹Ø¬ÙˆØ±Ù… Ù…Ø¤Ù„Ù Ø§Ù„ÙƒØªØ§Ø¨ Ù…Ù† Ø£ØªØ¨Ø§Ø¹ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙƒÙˆÙØ© ØŒ ÙˆÙŠØ¯Ù„ Ø¹Ù„Ù‰ Ø°Ù„Ùƒ Ø§Ù„Ø¹Ø¯ÙŠØ¯ Ù…Ù† Ø§Ù„Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ø§Ù„ÙƒÙˆÙØ© ÙˆØ§Ù„ØªÙŠ ØªØ³ØªØ®Ø¯Ù… Ø£ÙŠØ¶Ø§ ÙÙŠ ÙƒØªØ§Ø¨ Ø§Ù„Ø¬Ø±Ù…ÙŠØ© Ø¹Ù„Ù‰ Ø§Ù„Ù†ØÙˆ Ø§Ù„ØªØ§Ù„ÙŠ: (1) Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…ØµØ·Ù„Ø Ø§Ù„Ø®ÙØ¶ Ù„Ù„Ø¥Ø´Ø§Ø±Ø© Ø¥Ù„Ù‰ Ø§Ø¹Ø±Ø§Ø¨ Ø§Ø³Ù… Ø§Ù„Ø°ÙŠ ÙŠØªÙ…ÙŠØ² Ø¨ÙƒØ³Ø±Ù‡ ÙˆÙ„ÙŠØ³ Ø¬Ø± (2) Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…ØµØ·Ù„Ø "Ø§Ù„Ù…ÙØ¹ÙˆÙ„ Ø§Ù„Ø°ÙŠ Ù„Ù… ÙŠØ³Ù… ÙØ§Ø¹Ù„Ù‡ Ù„Ù…ØµØ·Ù„Ø Ø§Ù„ÙØ§Ø¹Ù„ ÙÙŠ Ø§Ù„ÙØ¹Ù„ Ø§Ù„Ù…Ø¨Ù†ÙŠ Ù„Ù„Ù…Ø¬Ù‡ÙˆÙ„ ØŒ ÙˆÙ„ÙŠØ³ Ù„Ù…ØµØ·Ù„Ø Ù†Ø§Ø¦Ø¨ Ø§Ù„ÙØ§Ø¹Ù„. (3) Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…ØµØ·Ù„Ø ÙƒÙŠÙ Ù…Ø§ Ù‡Ùˆ Ø¬Ø²Ø¡ Ù…Ù† Ø§Ù„Ø£ÙØ¹Ø§Ù„ Ø§Ù„Ø¬ÙˆØ§Ø²Ù… Ø£Ùˆ Ø¹Ø§Ù…Ù„ Ø§Ù„Ø°ÙŠ ÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠØ¶Ø¹ ÙØ¹Ù„ Ù…Ø¶Ø§Ø±Ø¹ ÙÙŠ Ù…Ø±ØªØ¨Ø© Ø§Ù„Ù…Ø¬Ø²ÙˆÙ… ÙƒÙ…Ø§ ÙŠØ¹ØªÙ‚Ø¯ Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„ÙƒÙˆÙØ©. (4) ÙˆØ¹Ù„Ø§Ù…Ø© Ø§Ù„Ø§Ø³Ù… Ù‡ÙŠ Ø¥Ø¯Ø±Ø§Ø¬ Ø§Ù„Ø£Ù„Ù ÙˆØ§Ù„Ù„Ø§Ù… ÙƒÙ…Ø§ ÙŠØ¹ØªÙ‚Ø¯ Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„ÙƒÙˆÙØ© ØŒ Ø£Ù…Ø§ Ø¹Ù†Ø¯ Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ø¨ØµØ±Ø© ÙØ¥Ù† Ù‡Ø°Ø§ Ù‡Ùˆ ØÙƒÙ… Ø§Ù„Ø£Ù„Ù ÙˆØ§Ù„Ù„Ø§Ù…. Ù„Ø§ Ø§Ù„Ø³ÙŠÙØ©. (6) Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø£Ø³Ù…Ø§Ø¡ Ø§Ù„Ø®Ø§Ù…Ø³Ø© ÙˆÙ‡ÙŠ Ø£Ø¨ÙˆÙƒØŒ Ø£Ø®ÙˆÙƒØŒ ØÙ…ÙˆÙƒØŒ ÙÙˆÙƒØŒ Ø°Ùˆ Ù…Ø§Ù„ØŒ Ø¨ÙŠÙ†Ù…Ø§ Ø§Ø³ØªØ®Ø¯Ù… Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ø¨ØµØ±Ø© Ø§Ù„Ø£Ø³Ù…Ø§Ø¡ Ø§Ù„Ø³ØªØ© Ø¨Ø¥Ø¶Ø§ÙØ© Ù‡Ù†ÙˆÙƒ.] This study discusses the Kufah Madrasah which has had a lot of influence on the development of Nahwu, especially on the use of terms in the Arabic grammatical book. This study used a literary study method and a qualitative approach to find out the influence of the Kufah madrasah on the book used by Indonesian students to learn Arabic, namely the al-Jurumiyah book. The results of the study show that Ibn Ajurrum, the author of the book, is a follower of the Kufa madrasah, this is indicated by the many terms used in the kufah madrasah which are also used in the al-Jurumiyah book as follows, (1) the use of the term al-khafd for i'rab isim which marked by kasroh, not the term jarr; (2) the use of the term al-maf'ul al-ladhi lam yusamma fa'iluh for the term subject in the passive verb, not the term na'ib al-fa'il; (3) the use of the term kayfama is part of al-af'al al-jawazim or of amil (particle) which can put fi'il mudari 'into the majzum position, as believed by kufah scholars; (4) the sign of a noun is the inclusion of alif and lam as believed by Kufah scholars, whereas according to the scholars of Basrah, this is the rule of alif and lam (5) the use of the term an-na'at, not al-sifah; (6) the use of al-asma al-khamsah, namely abuka, akhuka, hamuka, fuka, dhu mal, while Basrah scholars used al-asma al-siita by adding hanuka.